Revision of Neodeuterus Schaufuss and description of a new allied genus from Borneo (Coleoptera: Staphylinidae: Pselaphinae) - Kurbatov, Sergey A.; Cuccodoro, Giulio (Zootaxa, 2015)
The Sumatran genus Neodeuterus is revised, and the two included species are synonymized (i.e., N. admirandus = N. alter syn. n.). In addition, Borneodeuterus gen. n. is erected to accommodate B. sannio sp. n. from Borneo.